A review of regulatory instruments to control environmental externalities from the transport sector - Timilsina, Govinda R. (World Bank, 2009)
"This study reviews regulatory instruments designed to reduce environmental externalities from the transport sector. The study finds that the main regulatory instruments used in practice are fuel economy standards, vehicle emission standards, and fuel quality standards. Although industrialized countries have introduced all three standards with strong enforcement mechanisms, most developing countries have yet to introduce fuel economy standards. The emission standards introduced by many developing countries to control local air pollutants follow either the European Union or United States standards. Fuel quality standards, particularly for gasoline and diesel, have been introduced in many countries mandating 2 to 10 percent blending of biofuels, 10 to 50 times reduction of sulfur from 1996 levels, and banning lead contents. Although inspection and maintenance programs are in place in both industrialized and developing countries to enforce regulatory standards, these programs have faced several challenges in developing countries due to a lack of resources. The study also highlights several factors affecting the selection of regulatory instruments, such as countries' environmental priorities and institutional capacities. "--World Bank web site
Includes bibliographical references. - Title from PDF file as viewed on 5/8/2009
Keywords: Transportation -- Environmental aspects